RTB magnet and its manufacturing method
Optimizing the composition of R-T-B magnets with specific element percentages and forming a Cu-Nb-Fe phase in the grain boundaries addresses the limitations of existing neodymium iron boron magnets, enhancing magnetic properties for high-demand applications.
Patent Information
- Application Number
- JP2023544206
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-17
- Filing Date
- 2022-01-17
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2042-01-17
AI Technical Summary
Existing neodymium iron boron magnet materials do not achieve high levels of residual magnetic flux density, coercive force, high-temperature stability, and squareness ratio simultaneously, limiting their applicability in demanding products.
Optimizing the composition of R-T-B magnets by specific content percentages of elements such as Ti, Nb, Cu, and Fe, forming a Cu-Nb-Fe phase in the grain boundaries to enhance magnetic properties.
The optimized R-T-B magnets exhibit improved coercive force, residual magnetic flux density, and high-temperature stability, making them suitable for high-demand applications.
Smart Images

Figure 0007600414000004 
Figure 0007600414000001 
Figure 0007600414000002
Abstract
Description
[Technical field]
[0001] The present invention relates to RTB magnets and methods for making same. [Background technology]
[0002] NdFeB magnetic materials are currently widely used in the fields of electronics, power machinery, medical equipment, etc. In recent years, the improvement of the magnetic properties of NdFeB magnetic materials has become a current research hotspot.
[0003] For example, Chinese patent document CN108831650A discloses a NdFeB magnet material and its manufacturing method, which adopts the principle of small amount of multiple addition by adding 0.05-0.5% of titanium, zirconium, niobium, and gallium to NdFeB material, thereby reducing the amount of heavy rare earth elements in the material, unifying the second stage aging temperature of each brand, and improving the universality of the second stage aging. The addition of these four composite elements achieves the purpose of refining the crystal grains and improving the fluidity of the rare earth-rich phase at the grain boundary, improving the performance indexes of each item of the material, especially the intrinsic coercivity and squareness ratio, reducing the amount of heavy rare earth elements and improving the squareness ratio of the product, and improving the consistency and high temperature stability of the product. For example, the composition of Example 5 of the patent contains the following mass contents: 30.3% PrNd, 0% Dy, 0.97% B, 0.5% Co, 0.15% Cu, 0.1% Al, 0.08% Ti, 0.1% Nb, 0.2% Ga, 0.05% Zr, and the balance is Fe. A jet mill is used to produce 3.0 μm fine powder, and the sintering temperature is 1040°C, the first stage aging temperature is 900°C, and the second stage aging temperature is 520°C. Through the manufacturing process, a neodymium iron boron magnet material with a residual magnetic flux density of 14.4, Hcj of 12.5, a maximum energy product of 50.82, and a squareness ratio of 97% is obtained. However, the components of the magnet material have not been further optimized, and the coercive force of the obtained magnet material is at a low level, and the magnetic property temperature stability at high temperatures is also at a low level, so that it cannot be applied to products with higher requirements.
[0004] The current technical challenge to be solved is to determine the components of a neodymium iron boron magnet so as to obtain a magnet material that has excellent overall magnetic properties after manufacturing, such as high coercivity, high residual magnetic flux density, high temperature stability of coercivity, and high squareness ratio. Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention provides an RTB magnet and a manufacturing method thereof to solve the drawbacks of the prior art that the residual magnetic flux density, coercive force, high temperature stability and squareness ratio of the magnet obtained by the components of the NdFeB magnet material cannot reach high levels at the same time. By combining the types and contents of specific elements in the RTB magnet of the present invention, a magnet material with high residual magnetic flux density, coercive force and squareness ratio as well as excellent high temperature stability can be manufactured. [Means for solving the problem]
[0006] The present invention solves the above-mentioned technical problems mainly through the following technical ideas.
[0007] The present invention provides an RTB magnet, comprising the following components: R:≧30.0 wt.%, wherein R is a rare earth element; Nb: 0.02-0.14wt.%, Cu: 0.2-0.48 wt.%, Ti+Nb:≦0.24wt.%, Al+Cu:≦0.50wt.%, B: ≧0.955wt.%, Fe: 58 to 69 wt.%, where wt.% is the percentage that the mass of each component accounts for in the total mass of each component.
[0008] In the present invention, the content of R is preferably 30 to 33 wt.%, for example, 30 wt.%, 30.3 wt.%, or 30.8 wt.%.
[0009] In the present invention, the type of R can be any conventional in the art and generally includes Nd.
[0010] Here, the Nd content is preferably 29 to 31 wt.%, for example, 29 wt.%, 29.4 wt.%, 29.7 wt.%, 29.9 wt.%, 30 wt.%, 30.1 wt.%, or 30.4 wt.%, where wt.% is the percentage of the total mass of each component.
[0011] In the present invention, R generally further comprises Pr and / or RH, and RH is a heavy rare earth element.
[0012] Here, the Pr content is preferably 0.3 wt.% or less, where wt.% is the percentage of the mass of each component relative to the total mass of each component.
[0013] Here, the heavy rare earth element is preferably Tb.
[0014] Here, the content of RH may be 1.4 wt.% or less, for example, 0.2 wt.%, 0.4 wt.%, 0.6 wt.%, or 1 wt.%, where wt.% is the percentage of each component relative to the total mass.
[0015] Here, the ratio of the atomic percentage content of RH to the atomic percentage content of R may be less than or equal to 0.1, for example, 0.02, 0.04 or 0.06, and the atomic percentage content means the atomic percentage in the total content of each component.
[0016] In the present invention, the content of "Ti+Nb" is preferably 0.1 to 0.24 wt.%, for example, 0.1 wt.%, 0.2 wt.%, 0.23 wt.%, or 0.24 wt.%.
[0017] In the present invention, the Nb content is preferably 0.05 to 0.14 wt.%, for example, 0.05 wt.%, 0.09 wt.%, 0.1 wt.%, 0.12 wt.%, or 0.14 wt.%.
[0018] In the present invention, the Ti content is preferably 0.24 wt.% or less, but not 0 wt.%, and is, for example, 0.05 wt.%, 0.09 wt.%, 0.11 wt.%, 0.14 wt.%, or 0.15 wt.%.
[0019] In the present invention, the content of "Al+Cu" is preferably 0.44 wt.% or less, but is not 0 wt.%, and is more preferably 0.1 to 0.44 wt.%, for example, 0.23 wt.%, 0.25 wt.%, 0.32 wt.%, 0.33 wt.%, 0.34 wt.%, 0.43 wt.%, 0.44 wt.%, or 0.45 wt.%.
[0020] In the present invention, the Al content is preferably 0.08 wt.% or less, but is not 0 wt.%, and is, for example, 0.02 wt.%, 0.03 wt.%, 0.04 wt.%, 0.05 wt.%, 0.06 wt.%, or 0.08 wt.%.
[0021] In the present invention, the Cu content is preferably 0.2 to 0.46 wt.%, for example, 0.2 wt.%, 0.3 wt.%, 0.39 wt.%, 0.4 wt.%, or 0.46 wt.%.
[0022] In the present invention, the B content is preferably 0.955 to 1.15 wt.%, for example, 0.99 wt.%.
[0023] In the present invention, the ratio of the atomic percentage content of the B to the atomic percentage content of the R in the RTB magnet may be 0.38 or more, for example, 0.4, 0.41, 0.42, 0.43 or 0.44, and the atomic percentage content means the atomic percentage in the total content of each component.
[0024] In the present invention, the Fe content is preferably 67 to 69 wt.%, for example, 67.53 wt.%, 67.58 wt.%, 67.63 wt.%, 67.68 wt.%, 67.74 wt.%, 68.02 wt.%, 68.03 wt.%, 68.04 wt.%, 68.16 wt.%, 68.31 wt.%, 68.38 wt.%, 68.49 wt.%, 68.57 wt.%, or 68.58 wt.%.
[0025] In the present invention, the RTB magnet may further contain additive elements, such as Co, which are common in the art.
[0026] Here, the Co content is preferably 1 wt.% or less, for example, 0.8 wt.%, where wt.% is the percentage of the mass of each component relative to the total mass of each component.
[0027] In the present invention, as known to those skilled in the art, the RTB magnet may further contain unavoidable impurities during the manufacturing process, such as one or more of C, O and Mn.
[0028] The inventors have found that by optimizing the formulation of the RTB magnet, the magnetic properties such as coercivity, high temperature stability and squareness ratio of the RTB magnet obtained by the combination of the above specific contents of elements such as Ti, Nb, Cu, etc. are significantly improved. Furthermore, the inventors have found that the composition of the above specific components allows a part of Fe in the two-particle grain boundary phase to aggregate with Nb and Cu elements to form a Cu-Nb-Fe phase after the RTB magnet is manufactured, and the presence of the Cu-Nb-Fe phase significantly reduces the Fe content in the two-particle grain boundary phase, increasing the magnetic blocking effect of the Nd-rich phase, thereby obtaining the RTB magnet of the present invention.
[0029] In the present invention, the RTB magnet preferably further includes a Cu-Nb-Fe phase, and the Cu-Nb-Fe phase is located in an intergranular triangular region. The intergranular triangular region may have the meaning generally understood in the art, and generally means a grain boundary phase formed between three or more main phase grains. The grain boundary phase is generally a collective term for a region formed by a two-grain grain boundary phase and an intergranular triangular region. The two-grain grain boundary phase is generally a grain boundary phase between two main phase grains.
[0030] Here, the ratio of the area of the Cu-Nb-Fe phase in the intergranular triangular region to the total area of the intergranular triangular region is preferably 1.3 to 2%, for example, 1.3%, 1.4%, 1.5%, or 1.6%. In the present invention, the area of the Cu-Nb-Fe phase and the total area of the intergranular triangular region generally refer to the areas each occupy in the cross section of the RTB magnet detected by FE-EPMA.
[0031] Here, the ratio of the Fe content in the two-particle grain boundary phase to the total content of all elements in the two-particle grain boundary phase is preferably 46 wt.% or less, for example, 40 wt.%, 41 wt.%, 42 wt.%, 43 wt.%, 44 wt.%, 45 wt.%, or 46 wt.%. All elements in the two-particle grain boundary phase are, for example, Fe, rare earth elements, Cu, Nb, etc.
[0032] Here, it was found by measurement that the atomic percentage content ratio of Cu, Nb, and Fe in the Cu-Nb-Fe phase was close to 5:1:94. Therefore, in the present invention, the Cu-Nb-Fe phase is 5 Nb 1 Fe 94 It is preferred that the phase is
[0033] In one preferred embodiment of the present invention, the RTB magnet contains 29.4 wt.% Nd, 0.6 wt.% Tb, 0.3 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.49 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.4 wt.% Nd, 0.6 wt.% Tb, 0.3 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.49 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt.%.
[0034] In one preferred embodiment of the present invention, the RTB magnet contains 29.4 wt.% Nd, 0.6 wt.% Tb, 0.8 wt.% Co, 0.3 wt.% Cu, 0.03 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 67.68 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.4 wt.% Nd, 0.6 wt.% Tb, 0.8 wt.% Co, 0.3 wt.% Cu, 0.03 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 67.68 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 46 wt.%.
[0035] In one preferred embodiment of the present invention, the RTB magnet contains 29.4 wt.% Nd, 0.6 wt.% Tb, 0.5 wt.% Co, 0.2 wt.% Cu, 0.05 wt.% Al, 0.05 wt.% Nb, 0.05 wt.% Ti, 0.99 wt.% B and 68.16 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.4 wt.% Nd, 0.6 wt.% Tb, 0.5 wt.% Co, 0.2 wt.% Cu, 0.05 wt.% Al, 0.05 wt.% Nb, 0.05 wt.% Ti, 0.99 wt.% B and 68.16 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt.%.
[0036] In one preferred embodiment of the present invention, the RTB magnet contains 29.4 wt.% Nd, 0.6 wt.% Tb, 0.6 wt.% Co, 0.4 wt.% Cu, 0.04 wt.% Al, 0.14 wt.% Nb, 0.09 wt.% Ti, 0.99 wt.% B and 67.74 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.4 wt.% Nd, 0.6 wt.% Tb, 0.6 wt.% Co, 0.4 wt.% Cu, 0.04 wt.% Al, 0.14 wt.% Nb, 0.09 wt.% Ti, 0.99 wt.% B and 67.74 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.6%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 43 wt.%.
[0037] In one preferred embodiment of the present invention, the RTB magnet contains 29.4 wt.% Nd, 0.6 wt.% Tb, 0.2 wt.% Cu, 0.03 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.58 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.4 wt.% Nd, 0.6 wt.% Tb, 0.2 wt.% Cu, 0.03 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.58 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 43 wt.%.
[0038] In one preferred embodiment of the present invention, the RTB magnet contains 29.4 wt.% Nd, 0.6 wt.% Tb, 0.39 wt.% Cu, 0.04 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.38 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.4 wt.% Nd, 0.6 wt.% Tb, 0.39 wt.% Cu, 0.04 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.38 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 42 wt.%.
[0039] In one preferred embodiment of the present invention, the RTB magnet contains 29.4 wt.% Nd, 0.6 wt.% Tb, 0.46 wt.% Cu, 0.04 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.31 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.4 wt.% Nd, 0.6 wt.% Tb, 0.46 wt.% Cu, 0.04 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.31 wt.% Fe.5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 46 wt.%.
[0040] In one preferred embodiment of the present invention, the RTB magnet contains 29.4 wt.% Nd, 0.6 wt.% Tb, 0.3 wt.% Cu, 0.04 wt.% Al, 0.05 wt.% Nb, 0.05 wt.% Ti, 0.99 wt.% B and 68.57 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.4 wt.% Nd, 0.6 wt.% Tb, 0.3 wt.% Cu, 0.04 wt.% Al, 0.05 wt.% Nb, 0.05 wt.% Ti, 0.99 wt.% B and 68.57 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 44 wt.%.
[0041] In one preferred embodiment of the present invention, the RTB magnet contains 29.4 wt.% Nd, 0.6 wt.% Tb, 0.8 wt.% Co, 0.3 wt.% Cu, 0.03 wt.% Al, 0.1 wt.% Nb, 0.14 wt.% Ti, 0.99 wt.% B and 67.64 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.4 wt.% Nd, 0.6 wt.% Tb, 0.8 wt.% Co, 0.3 wt.% Cu, 0.03 wt.% Al, 0.1 wt.% Nb, 0.14 wt.% Ti, 0.99 wt.% B and 67.64 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 43 wt.%.
[0042] In one preferred embodiment of the present invention, the RTB magnet contains 29.4 wt.% Nd, 0.6 wt.% Tb, 0.8 wt.% Co, 0.3 wt.% Cu, 0.03 wt.% Al, 0.12 wt.% Nb, 0.11 wt.% Ti, 0.99 wt.% B and 67.65 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.4 wt.% Nd, 0.6 wt.% Tb, 0.8 wt.% Co, 0.3 wt.% Cu, 0.03 wt.% Al, 0.12 wt.% Nb, 0.11 wt.% Ti, 0.99 wt.% B and 67.65 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt.%.
[0043] In one preferred embodiment of the present invention, the RTB magnet contains 29.7 wt.% Nd, 0.6 wt.% Tb, 0.39 wt.% Cu, 0.04 wt.% Al, 0.1 wt.% Nb, 0.14 wt.% Ti, 0.99 wt.% B and 68.04 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.7 wt.% Nd, 0.6 wt.% Tb, 0.39 wt.% Cu, 0.04 wt.% Al, 0.1 wt.% Nb, 0.14 wt.% Ti, 0.99 wt.% B and 68.04 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.6%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt.%.
[0044] In one preferred embodiment of the present invention, the RTB magnet contains 30.4 wt.% Nd, 0.4 wt.% Tb, 0.39 wt.% Cu, 0.05 wt.% Al, 0.1 wt.% Nb, 0.14 wt.% Ti, 0.99 wt.% B and 67.53 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 30.4 wt.% Nd, 0.4 wt.% Tb, 0.39 wt.% Cu, 0.05 wt.% Al, 0.1 wt.% Nb, 0.14 wt.% Ti, 0.99 wt.% B and 67.53 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt.%.
[0045] In one preferred embodiment of the present invention, the RTB magnet contains 29.9 wt.% Nd, 0.4 wt.% Tb, 0.39 wt.% Cu, 0.06 wt.% Al, 0.1 wt.% Nb, 0.14 wt.% Ti, 0.99 wt.% B and 68.02 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.9 wt.% Nd, 0.4 wt.% Tb, 0.39 wt.% Cu, 0.06 wt.% Al, 0.1 wt.% Nb, 0.14 wt.% Ti, 0.99 wt.% B and 68.02 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 43 wt.%.
[0046] In one preferred embodiment of the present invention, the RTB magnet contains 30.1 wt.% Nd, 0.2 wt.% Tb, 0.39 wt.% Cu, 0.05 wt.% Al, 0.09 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.03 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 30.1 wt.% Nd, 0.2 wt.% Tb, 0.39 wt.% Cu, 0.05 wt.% Al, 0.09 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.03 wt.% Fe.5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 44 wt.%.
[0047] In one preferred embodiment of the present invention, the RTB magnet contains 29.4 wt.% Nd, 0.6 wt.% Tb, 0.3 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.49 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.4 wt.% Nd, 0.6 wt.% Tb, 0.3 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.49 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 42 wt.%.
[0048] In one preferred embodiment of the present invention, the RTB magnet contains 29.4 wt.% Nd, 0.6 wt.% Tb, 0.3 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.49 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29.4 wt.% Nd, 0.6 wt.% Tb, 0.3 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.49 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt.%.
[0049] In one preferred embodiment of the present invention, the RTB magnet contains 30 wt.% Nd, 0.3 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.49 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain Cu. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 43 wt.%.
[0050] In one preferred embodiment of the present invention, the RTB magnet contains 29 wt.% Nd, 1 wt.% Tb, 0.3 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.49 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 29 wt.% Nd, 1 wt.% Tb, 0.3 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.49 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt.%.
[0051] In one preferred embodiment of the present invention, the RTB magnet contains 28.2 wt.% Nd, 0.6 wt.% Tb, 1.2 wt.% Dy, 0.36 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.43 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 28.2 wt.% Nd, 0.6 wt.% Tb, 1.2 wt.% Dy, 0.36 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.43 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 44 wt.%.
[0052] In one preferred embodiment of the present invention, the RTB magnet contains 28.4 wt.% Nd, 0.6 wt.% Tb, 1 wt.% Dy, 0.5 wt.% Co, 0.36 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 67.93 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 28.4 wt.% Nd, 0.6 wt.% Tb, 1 wt.% Dy, 0.5 wt.% Co, 0.36 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 67.93 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.3%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 46 wt.%.
[0053] In one preferred embodiment of the present invention, the RTB magnet contains 28.8 wt.% Nd, 0.6 wt.% Tb, 0.6 wt.% Dy, 0.36 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.43 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 28.8 wt.% Nd, 0.6 wt.% Tb, 0.6 wt.% Dy, 0.36 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.43 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.3%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 46 wt.%.
[0054] In one preferred embodiment of the present invention, the RTB magnet contains 28.2 wt.% Nd, 0.7 wt.% Tb, 0.3 wt.% Dy, 0.8 wt.% Co, 0.36 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.43 wt.% Fe, where wt.% is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the RTB magnet contain 28.2 wt.% Nd, 0.7 wt.% Tb, 0.3 wt.% Dy, 0.8 wt.% Co, 0.36 wt.% Cu, 0.02 wt.% Al, 0.05 wt.% Nb, 0.15 wt.% Ti, 0.99 wt.% B and 68.43 wt.% Fe. 5 Nb 1 Fe 94 phase, 5 Nb 1 Fe 94 The ratio of the area of the phase to the total area of the intergranular triangular regions is 1.3%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 46 wt.%.
[0055] The present invention further provides a method for producing the above RTB magnet, the method comprising the steps of pulverizing a raw material mixture of the components and then sintering the mixture, The particle size of the powder obtained after the fine pulverization is 3.9 to 4.4 μm.
[0056] In the present invention, the particle size of the powder obtained after the fine pulverization is, for example, 3.9 μm, 4.0 μm, 4.1 μm, 4.2 μm or 4.3 μm.
[0057] In the present invention, the inventors have found that in the process of producing the RTB magnet, if the particle size of the powder obtained after the pulverization is larger than 4.4 μm or smaller than 3.9 μm, the area ratio of the Cu-Nb-Fe phase in the triangular region between crystal grains of the RTB magnet decreases. The particle size of the powder is generally D50.
[0058] In the present invention, the fine pulverization step may be carried out by a method commonly used in the art, such as jet mill pulverization.
[0059] Here, the gas atmosphere during the fine pulverization may have an oxidizing gas content of 1000 ppm or less, and the oxidizing gas content means the content of oxygen or moisture.
[0060] Here, the pressure during the fine pulverization is, for example, 0.68 MPa.
[0061] Here, after said milling, a further lubricant, such as zinc stearate, is generally added.
[0062] Here, the amount of the lubricant added may be 0.05 to 0.15% of the powder mass obtained after the fine pulverization, and is, for example, 0.12%.
[0063] In the present invention, the sintering temperature may be a temperature commonly used in this field, and is preferably 1000 to 1100°C, for example 1080°C.
[0064] In the present invention, the sintering process is preferably carried out under vacuum conditions, for example, 5×10 -3 The experiment was carried out under vacuum conditions of 10 Pa.
[0065] In the present invention, the sintering time can be a time commonly used in the art, and may be 4 to 8 hours, for example, 6 hours.
[0066] As will be appreciated by those skilled in the art, the present invention generally further includes subjecting the raw material mixture of each component of the RTB magnet to smelting, casting and hydro-crushing in sequence prior to the pulverization.
[0067] Here, the smelting and refining process may be a typical smelting and refining process in the art.
[0068] The vacuum level during the melting and smelting is, for example, 5×10 -2 It is Pa.
[0069] The temperature of the smelting is, for example, 1550° C. or lower.
[0070] The melting and refining is generally carried out in a high-frequency vacuum induction melting furnace.
[0071] Here, the casting process may be a common one used in the art.
[0072] Here, the casting process employs, for example, strip casting.
[0073] Here, the casting temperature may be 1390 to 1460°C, for example, 1400, 1420°C, or 1430°C.
[0074] Here, the thickness of the alloy flakes obtained after the casting may be 0.25 to 0.40 mm, for example, 0.29 mm.
[0075] Here, the hydrofractionation process may generally be carried out in the order of hydrogen absorption, dehydrogenation, and cooling treatment.
[0076] The hydrogen absorption can be carried out under the condition of a hydrogen gas pressure of 0.085 MPa.
[0077] The dehydrogenation can be carried out under conditions of evacuation and heating. The dehydrogenation temperature may be 480 to 520°C, and is, for example, 500°C.
[0078] In the present invention, after the fine pulverization and before the sintering treatment, a molding step as is commonly used in the art is generally included.
[0079] Here, the molding may be performed by using a magnetic field molding method.
[0080] Here, the compaction is carried out under the protection of a nitrogen atmosphere with a magnetic field strength of 1.8 T or more, for example, a magnetic field strength of 1.8 to 2.5 T.
[0081] In the present invention, the sintering step is generally followed by an ageing treatment as is customary in the art.
[0082] Generally, the aging treatment includes a first stage aging treatment and a second stage aging treatment.
[0083] The temperature of the first stage aging treatment may be 860 to 920°C, for example, 880°C or 900°C.
[0084] The time for the first stage aging treatment may be 2.5 to 4 hours, for example, 3 hours.
[0085] The temperature of the second stage aging treatment may be 460 to 530°C, for example, 490°C, 500°C, 510°C, or 520°C.
[0086] The time for the second stage aging treatment may be 2.5 to 4 hours, for example, 3 hours.
[0087] In the present invention, when the RTB magnet further comprises a heavy rare earth element, it generally further comprises grain boundary diffusion after the aging treatment.
[0088] Here, the grain boundary diffusion may be a common process in the art, and it is common to diffuse a heavy rare earth element through the grain boundaries.
[0089] The temperature of the grain boundary diffusion may be 800 to 900° C., for example, 850° C. The time of the grain boundary diffusion may be 5 to 10 hours, for example, 8 hours.
[0090] Here, the method of adding heavy rare earth elements to the RTB magnet can be referred to in the art, and generally, 0-80% of the heavy rare earth elements are added during melting and refining, and the remainder is added during melting and refining, for example, 33%, 38%, 40%, 57% or 67%. The heavy rare earth element added during melting and refining is, for example, Tb.
[0091] For example, if the heavy rare earth element in the RTB magnet is Tb and Tb is greater than 0.5 wt.%, 40-67% of Tb is added during melting and smelting, and the remainder is added during grain boundary diffusion. For example, if the heavy rare earth elements in the RTB magnet are Tb and Dy, Tb is added during melting and smelting, and Dy is added during grain boundary diffusion. For example, if the heavy rare earth element in the RTB magnet is Tb and Tb is 0.5 wt.% or less, or if the heavy rare earth element in the RTB magnet is Dy, the heavy rare earth element in the RTB magnet is added during grain boundary diffusion.
[0092] In the present invention, when the RTB magnet contains less than 0.08 wt.% Al, no additional Al is typically added when preparing the raw material mixture of each component. Those skilled in the art know that less than 0.08 wt.% Al is typically introduced during the manufacturing process.
[0093] The present invention further provides an RTB magnet obtained by employing the above-mentioned manufacturing method.
[0094] By arbitrarily combining each of the above-mentioned preferred conditions in accordance with the common general knowledge in this field, each preferred embodiment of the present invention can be obtained.
[0095] All of the reagents and raw materials used in the present invention are commercially available. Effect of the Invention
[0096] The positive and progressive effects of the present invention are as follows: the present invention further optimizes the components of the RTB magnet through the blending of specific contents of elements such as Ti, Nb, Cu, etc., so that the coercivity of the obtained RTB magnet is significantly improved, and the magnetic properties such as residual magnetic flux density, high stability performance, and squareness ratio are also at high levels. [Brief description of the drawings]
[0097] [Figure 1] FIG. 1 is a SEM map of the RTB magnet in Example 1, where the location indicated by arrow a in FIG. 1 is the Cu—Nb—Fe phase of a single point quantitative analysis in the intergranular triangular region. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0098] The present invention will be further described below with reference to examples, but the present invention is not limited to the scope of the examples. In the following examples, the experimental methods for which no specific conditions are specified are selected according to the usual methods and conditions or according to the product specifications. Example 1
[0099] Raw materials were prepared according to the components of the RTB magnet of Example 1 shown in Table 1 below, and the raw material mixture (in Table 1, 0.4 wt. % Tb was added during melting and smelting, and the remaining 0.2 wt. % was added during the grain boundary diffusion described below) was subjected to melting and smelting, casting, hydrogen crushing, pulverization, magnetic field compaction, sintering, aging treatment, and grain boundary diffusion in that order to obtain the magnet.
[0100] Here, the melting and smelting process is carried out under a vacuum of 5×10 -2 The melting and smelting process is carried out in a high-frequency vacuum induction furnace with a melting temperature of 1530°C or less.
[0101] The casting is carried out by strip casting method to obtain alloy strips with a thickness of 0.29mm, and the casting temperature is 1420℃.
[0102] Hydrogen crushing is carried out in the following order: hydrogen absorption, dehydrogenation, and cooling. Hydrogen absorption can be carried out under hydrogen pressure of 0.085 MPa. Dehydrogenation is carried out under conditions of evacuation and heating, and the dehydrogenation temperature is 500°C.
[0103] The fine pulverization is performed by jet mill pulverization in an atmosphere with an oxidizing gas content of 100 ppm or less, and the particle size of the obtained powder is 4.1 μm, where oxidizing gas means oxygen or water content. The pressure in the grinding chamber for the jet mill pulverization is 0.68 MPa. After pulverization, zinc stearate, a lubricant, is added in an amount of 0.12% of the powder weight after mixing.
[0104] Magnetic field compaction was carried out under the protection of a magnetic field strength of 1.8–2.5 T and nitrogen atmosphere.
[0105] Sintering is 5×10 -3 Sintering is carried out under vacuum conditions of 100 Pa and 1080° C. for 6 h, and then cooled, and Ar gas can be introduced before cooling so that the pressure reaches 0.05 MPa.
[0106] Aging treatment: the first stage aging temperature is 900℃, the time is 3h, the second stage aging temperature is 490℃, the time is 3h.
[0107] Grain boundary diffusion: The remaining heavy rare earth elements (0.2 wt.% Tb) are attached to the surface of the material, and grain boundary diffusion is carried out at 850°C for 8 hours.
[0108] 2. The raw materials and powder particle sizes of the RTB magnets in Examples 2-22 and Comparative Examples 1-7 are as shown in Table 1, and the other manufacturing steps are performed according to Example 1. Here, in Examples 1-11, 15, 16, 18 and Comparative Examples 1-7, 0.4 wt% Tb is added during melting and smelting, and the remaining Tb enters the RTB magnets by grain boundary diffusion, while in Examples 12-14 the heavy rare earth elements are added during grain boundary diffusion, and in Example 17 there is no grain boundary diffusion. In Examples 19-22, Tb is added during melting and smelting, and Dy is added during grain boundary diffusion. Effect Example 1
[0109] 1. Component measurement: The RTB permanent magnet materials in Examples 1 to 22 and Comparative Examples 1 to 7 were measured using a high-frequency inductively coupled plasma optical emission spectrometer (ICP-OES). The test results are shown in Table 1.
[0110] Table 1. Composition and content of RTB magnets (wt%) Table 1 JPEG0007600414000001.jpg196161
[0111] Note: / indicates that the element was not detected. Ga and Zr were not detected in the RTB magnets of the above examples and comparative examples. C, O, and Mn are inevitably introduced into the final RTB magnets during manufacturing, and the contents listed in the examples and comparative examples do not include these impurities. Also, 0.08wt% or less of Al was introduced during the manufacturing process and was not specifically added in the form of a raw material.
[0112] 2. Magnetic property test The RTB magnets in Examples 1-22 and Comparative Examples 1-7 were tested using a PFM pulse-type BH demagnetization curve tester to obtain data on residual magnetic flux density (Br), intrinsic coercivity (Hcj), maximum energy product (BHmax) and squareness ratio (Hk / Hcj), and the test results are shown in Table 2 below.
[0113] Table 2 JPEG0007600414000002.jpg196161
[0114] 3. Microstructure testing Detection by FE-EPMA: The vertically oriented surfaces of the RTB magnets in Examples 1-22 and Comparative Examples 1-7 were polished and detected by adopting a field emission electron probe microanalyzer (FE-EPMA, JEOL, 8530F). First, the distribution of elements such as Cu, Nb, Fe, etc. in the RTB magnet was determined by FE-EPMA surface scanning, and then the contents of elements such as Cu, Nb, Fe, etc. in the Cu-Nb-Fe phase were determined by FE-EPMA single-point quantitative analysis, and the test conditions were an acceleration voltage of 15 kv and a probe beam current of 50 nA. According to the measurement, the atomic ratio of Cu, Nb, Fe elements in the Cu-Nb-Fe phase in Examples 1-18 was close to 5:1:94, and therefore the Cu-Nb-Fe phase was found to be composed of Cu, Nb, Fe, and Fe atoms. 5 Nb 1 Fe 94 It is a phase.
[0115] As shown in Figure 1, Figure 1 is a SEM map of the RTB magnet obtained by FE-EPMA detection in Example 1, and the position indicated by the arrow a in Figure 1 is the Cu-Nb-Fe phase of the single point quantitative analysis in the intergranular triangular region. Through measurement and calculation, it was found that the intergranular triangular region of the RTB magnet of the present invention contains Cu. 5 Nb 1 Fe 94 phase and Cu 5 Nb 1 Fe 94 The ratio of the area of the Cu phase to the total area of the intergranular triangular regions is 1.5%. 5 Nb 1 Fe 94 The area of the phase and the total area of the intergranular triangular region refer to the areas occupied by the cross section (the vertically oriented surface mentioned above) of the RTB magnet detected during FE-EPMA detection. In addition, as a result of analyzing the Fe content in the two-particle grain boundary phase by FE-EPMA measurement, it was found that the ratio of the Fe content in the two-particle grain boundary phase to the total content of all elements in the two-particle grain boundary phase was 45wt.%.
[0116] The results of FE-EPMA detection in Examples 1 to 22 and Comparative Examples 1 to 7 are shown in Table 3 below.
[0117] Table 3 JPEG0007600414000003.jpg192161
[0118] As can be seen from the above experimental data, the components of the RTB magnet designed by the inventors, after being manufactured into a magnetic material, all have high levels of residual magnetic flux density, coercive force, high temperature stability, magnetic energy product and squareness ratio, making it possible to obtain a magnetic material with excellent overall magnetic properties and capable of satisfying applications in highly demanding fields. Through further analysis of the microstructure, the inventors have found that, after an RTB magnet of the above specific components is manufactured into a magnetic material, a specific area percentage of Cu is present in the triangular regions between the crystal grains of the magnet. 5 Nb 1 Fe 94 They discovered that a neodymium-rich phase is formed, and that the presence of this phase collects the Fe elements distributed in the two-particle grain boundary phase, thereby reducing the Fe distributed in the two-particle grain boundary phase, strengthening the magnetic blocking effect of the neodymium-rich phase, and further improving the magnetic properties.
[0119] If the content of certain elements in the composition of the RTB magnet is outside the range of this invention, a small amount of Cu 5 Nb 1 Fe 94 For example, in Comparative Example 1, the Cu content is too low, so Cu gathers only at the phase interface between the main phase and the grain boundary phase, and there is no Cu in the grain boundary phase. 5 Nb 1 Fe 94 For example, in Comparative Example 4, Al+Cu is greater than 0.5 wt.%, and too much Cu enters the grain boundary phase, reducing the interface stability and preventing the formation of Cu. 5 Nb 1 Fe 94 For example, in Comparative Example 5, Nb+Ti is greater than 0.24 wt.%, and too many high melting point elements pin the grain boundaries, affecting the fluidity of the Nd-rich phase, and Cu 5 Nb1 Fe 94 This leads to a decrease in the content of the phase.
Claims
1. An R-T-B magnet, Contains the following ingredients: R: ≧30.0 wt. %, where R is a rare earth element; Nb: 0.02 to 0.14wt. %, Cu: 0.2 to 0.48wt. %, Ti+Nb:≦0.24wt. %, Al+Cu:≦0.50wt. %, B: ≧0.955wt. %, The balance is Fe, and wt. % is the percentage of the mass of each component relative to the total mass of each component. the ratio of the Fe content in the two-particle grain boundary phase of the R-T-B magnet to the total content of all elements in the two-particle grain boundary phase is 40 wt. % to 46 wt. %, the R-T-B magnet contains a Cu-Nb-Fe phase, the Cu-Nb-Fe phase being located in intergranular triangular regions; The ratio of the area of the Cu—Nb—Fe phase to the total area of the intergrain triangular regions is 1.3 to 2%; The ratio of the atomic percentage contents of Cu, Nb, and Fe in the Cu-Nb-Fe phase is 5:1:94; The RTB magnet is characterized by:
2. The content of R is 30 to 33 wt. %, The type of R includes Nd, Here, the content of Nd is 29 to 31 wt. %, where wt. % is the percentage of the total mass of each component, The type of R further includes at least one of Pr and RH, wherein RH is a heavy rare earth element; Here, the content of Pr is 0.3 wt. % or less, where wt. % is the percentage of each component in the total mass, Here, the type of RH is Tb, Here, the content of RH is 1.4 wt. % or less, where wt. % is the percentage of each component in the total mass, wherein the ratio of the atomic percentage content of RH to the atomic percentage content of R is 0.1 or less; 2. The RTB magnet according to claim 1 .
3. The content of the "Ti + Nb" is 0.1 to 0.24 wt.%, The Nb content is 0.05 to 0.14 wt. %, The Ti content is 0.24 wt. % or less, but not 0 wt. %; The content of "Al+Cu" is 0.44 wt.% or less, but not 0 wt.%, The content of Al is 0.08 wt. % or less, but not 0 wt. %, The Cu content is 0.2 to 0.46 wt. %.
2. The RTB magnet according to claim 1 .
4. The content of B is 0.955 to 1.15 wt. %, the ratio of the atomic percentage content of the B to the atomic percentage content of the R in the R-T-B magnet is 0.38 or more; The R-T-B magnet further comprises Co, Here, the Co content is 1 wt. % or less.
2. The RTB magnet according to claim 1 .
5. The ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 42 wt.%, 43 wt.%, 44 wt.%, 45 wt.%, or 46 wt.%, The ratio of the area of the Cu—Nb—Fe phase to the total area of the intergranular triangular regions is 1.3%, 1.4%, 1.5%, or 1.6%; 2. The RTB magnet according to claim 1 .
6. The R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.3 wt. % Cu, 0.02 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B, and 68.49 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.3 wt. % Cu, 0.02 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B, and 68.49 wt. % Fe in the triangular regions between crystal grains. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt. %; Alternatively, the R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.8 wt. % Co, 0.3 wt. % Cu, 0.03 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B, and 67.68 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 46 wt. %; Alternatively, the R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.5 wt. % Co, 0.2 wt. % Cu, 0.05 wt. % Al, 0.05 wt. % Nb, 0.05 wt. % Ti, 0.99 wt. % B, and 68.16 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt. %; Alternatively, the R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.6 wt. % Co, 0.4 wt. % Cu, 0.04 wt. % Al, 0.14 wt. % Nb, 0.09 wt. % Ti, 0.99 wt. % B, and 67.74 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu, 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular regions is 1.6%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 43 wt. %; Alternatively, the R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.2 wt. % Cu, 0.03 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B and 68.58 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 43 wt. %; Alternatively, the R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.39 wt. % Cu, 0.04 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B and 68.38 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular regions is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 42 wt. %; Alternatively, the R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.46 wt. % Cu, 0.04 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B and 68.31 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular regions is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 46 wt. %; Alternatively, the R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.3 wt. % Cu, 0.04 wt. % Al, 0.05 wt. % Nb, 0.05 wt. % Ti, 0.99 wt. % B, and 68.57 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 44 wt. %; Alternatively, the R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.8 wt. % Co, 0.3 wt. % Cu, 0.03 wt. % Al, 0.1 wt. % Nb, 0.14 wt. % Ti, 0.99 wt. % B, and 67.64 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 43 wt. %; Alternatively, the R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.8 wt. % Co, 0.3 wt. % Cu, 0.03 wt. % Al, 0.12 wt. % Nb, 0.11 wt. % Ti, 0.99 wt. % B, and 67.65 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt. %; Alternatively, the R-T-B magnet contains 29.7 wt. % Nd, 0.6 wt. % Tb, 0.39 wt. % Cu, 0.04 wt. % Al, 0.1 wt. % Nb, 0.14 wt. % Ti, 0.99 wt. % B, and 68.04 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.6%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt. %; Alternatively, the R-T-B magnet contains 30.4 wt. % Nd, 0.4 wt. % Tb, 0.39 wt. % Cu, 0.05 wt. % Al, 0.1 wt. % Nb, 0.14 wt. % Ti, 0.99 wt. % B and 67.53 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu, 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt. %; Alternatively, the R-T-B magnet contains 29.9 wt. % Nd, 0.4 wt. % Tb, 0.39 wt. % Cu, 0.06 wt. % Al, 0.1 wt. % Nb, 0.14 wt. % Ti, 0.99 wt. % B, and 68.02 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 43 wt. %; Alternatively, the R-T-B magnet contains 30.1 wt. % Nd, 0.2 wt. % Tb, 0.39 wt. % Cu, 0.05 wt. % Al, 0.09 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B and 68.03 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 44 wt. %; Alternatively, the R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.3 wt. % Cu, 0.02 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B and 68.49 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular regions is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 42 wt. %; Alternatively, the R-T-B magnet contains 29.4 wt. % Nd, 0.6 wt. % Tb, 0.3 wt. % Cu, 0.02 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B and 68.49 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt. %; Alternatively, the R-T-B magnet contains 30 wt. % Nd, 0.3 wt. % Cu, 0.02 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B and 68.49 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular region of the R-T-B magnet contains Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.5%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 43 wt. %; Alternatively, the R-T-B magnet contains 29 wt. % Nd, 1 wt. % Tb, 0.3 wt. % Cu, 0.02 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B and 68.49 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the R-T-B magnet contains 29 wt. % Nd, 1 wt. % Tb, 0.3 wt. % Cu, 0.02 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B and 68.49 wt. % Fe in the triangular regions between crystal grains. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 45 wt. %; Alternatively, the R-T-B magnet contains 28.2 wt. % Nd, 0.6 wt. % Tb, 1.2 wt. % Dy, 0.36 wt. % Cu, 0.02 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B, and 68.43 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.4%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 44 wt. %; Alternatively, the R-T-B magnet contains 28.4 wt. % Nd, 0.6 wt. % Tb, 1 wt. % Dy, 0.5 wt. % Co, 0.36 wt. % Cu, 0.02 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B and 67.93 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu, 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.3%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 46 wt. %; Alternatively, the R-T-B magnet contains 28.8 wt. % Nd, 0.6 wt. % Tb, 0.6 wt. % Dy, 0.36 wt. % Cu, 0.02 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B, and 68.43 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu. 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.3%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 46 wt. %; Alternatively, the R-T-B magnet contains 28.2 wt. % Nd, 0.7 wt. % Tb, 0.3 wt. % Dy, 0.8 wt. % Co, 0.36 wt. % Cu, 0.02 wt. % Al, 0.05 wt. % Nb, 0.15 wt. % Ti, 0.99 wt. % B, and 68.43 wt. % Fe, where wt. % is the mass ratio of the content of each component to the total content of each component, and the intergranular triangular regions of the R-T-B magnet contain Cu, 5 Nb 1 Fe 94 The Cu phase is further included. 5 Nb 1 Fe 94 The ratio of the area of the two-grain grain boundary phase to the total area of the intergranular triangular region is 1.3%, and the ratio of the Fe content in the two-grain grain boundary phase to the total content of all elements in the two-grain grain boundary phase is 46 wt.%.
2. The RTB magnet according to claim 1 .
7. A method for producing an R-T-B magnet, comprising the steps of: The method includes the steps of: pulverizing a raw material mixture of each component of the R-T-B magnet according to any one of claims 1 to 6, and then sintering the mixture; The particle size of the powder obtained after the milling is 3.9 to 4.4 μm. The present invention relates to a method for producing an RTB magnet.
8. The particle size of the powder obtained after the milling is 3.9 μm, 4.0 μm, 4.1 μm, 4.2 μm or 4.3 μm, The fine pulverization is jet mill pulverization, The gas atmosphere during the fine pulverization has an oxidizing gas content of 1000 ppm or less, the oxidizing gas content meaning the content of oxygen or moisture; The sintering temperature is 1000 to 1100° C. The sintering time is 4 to 8 hours, The method further includes, before the fine grinding, sequentially subjecting the raw material mixture of each component of the R-T-B magnet to melting, casting, and hydro-crushing; Here, the vacuum degree of the melting and smelting is 5×10 -2 Pa, Here, the temperature of the melting and smelting is 1550° C. or less, Here, the casting step employs a rapid solidification casting method, wherein the casting temperature is 1390 to 1460°C; wherein the thickness of the alloy flake obtained after the casting is 0.25 to 0.40 mm; After the pulverization and before the sintering process, a magnetic field molding is included; 8. The method for producing an RTB magnet according to claim 7.
9. The method further comprises aging treatment after the sintering treatment, Here, the aging treatment includes a first stage aging treatment and a second stage aging treatment, The temperature of the first stage aging treatment is 860 to 920°C, The time of the first stage aging treatment is 2.5 to 4 hours, The temperature of the second stage aging treatment is 460 to 530°C, The second stage aging treatment is performed for a period of 2.5 to 4 hours. Wherein, when the R-T-B magnet further contains a heavy rare earth element, the R-T-B magnet generally further includes grain boundary diffusion after the aging treatment, the temperature of the grain boundary diffusion being 800 to 900° C., and the time of the grain boundary diffusion being 5 to 10 hours; The method of adding heavy rare earth elements in the R-T-B magnet is to add 0-80% of the heavy rare earth elements during melting and refining, and the remaining heavy rare earth elements during melting and refining; if the heavy rare earth element in the R-T-B magnet is Tb and Tb is greater than 0.5 wt.%, 40-67% of Tb is added during melting and refining, and the remaining is added during grain boundary diffusion; if the heavy rare earth elements in the R-T-B magnet are Tb and Dy, Tb is added during melting and refining, and Dy is added during grain boundary diffusion; if the heavy rare earth element in the R-T-B magnet is Tb and Tb is 0.5 wt.% or less, or if the heavy rare earth element in the R-T-B magnet is Dy, the heavy rare earth element in the R-T-B magnet is added during grain boundary diffusion; 8. The method for producing an RTB magnet according to claim 7.
10. An RTB magnet produced by the method for producing an RTB magnet according to claim 7.
Citation Information
Patent Citations
High ant-erosion and high performance R-Fe-B agglomeration magnetic body and its making method
CN101266856A
